2017
DOI: 10.1111/jcpe.12664
|View full text |Cite
|
Sign up to set email alerts
|

The subgingival microbiome, systemic inflammation and insulin resistance: The Oral Infections, Glucose Intolerance and Insulin Resistance Study

Abstract: Background Inflammation might link microbial exposures to insulin resistance. We investigated the cross-sectional association between periodontal microbiota, inflammation and insulin resistance. Methods The Oral Infections, Glucose Intolerance and Insulin Resistance Study (ORIGINS) enrolled 152 diabetes-free adults (77% female) aged 20–55 years (mean=34±10). 304 subgingival plaque samples were analyzed using the Human Oral Microbe Identification Microarray to measure the relative abundances of 379 taxa. C-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
76
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 55 publications
13
76
1
2
Order By: Relevance
“…In a large study by DESVARIEUX and coworkers, an overall subgingival bacterial burden (11 species) was not associated with CRP concentration or white blood cell count . In a more recent work, a systemic inflammatory score was inversely associated with actinobacteria and proteobacteria and directly with Firmicutes and the candidate phylum, TM7 . Before correction for multiple comparisons, the study revealed 18 individual taxa associating with the inflammatory score.…”
Section: Oral Microbiota and Cvdmentioning
confidence: 78%
“…In a large study by DESVARIEUX and coworkers, an overall subgingival bacterial burden (11 species) was not associated with CRP concentration or white blood cell count . In a more recent work, a systemic inflammatory score was inversely associated with actinobacteria and proteobacteria and directly with Firmicutes and the candidate phylum, TM7 . Before correction for multiple comparisons, the study revealed 18 individual taxa associating with the inflammatory score.…”
Section: Oral Microbiota and Cvdmentioning
confidence: 78%
“…This shift increases pathogenicity as shown by changes in the oral cavity of diabetic mice including higher levels of Proteobacteria ( Enterobacteriaceae ) and Firmicutes ( Enterococcus, Staphylococcus and Aerococcus ) that are associated with infectious processes, periodontitis and delayed wound healing in diabetic animals (Grice et al, 2010a; Souto and Colombo, 2008; Vieira Colombo et al, 2016). Overall, the Firmicutes phylum is positively associated with periodontitis and insulin resistance (Demmer et al, 2016). Enterococcus was also the predominant taxa in recipient mice which had bacteria transferred from diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…The differential oral microbial patterns noted in our study may result in a differential effect on metabolic alterations. Indeed, oral TM7 has been associated with a higher inflammatory score (60), a high risk of periodontitis and with human inflammatory mucosal diseases (61). Furthermore, Fusobacterium species have an important function in the subgingival biofilm which allows periodontal bacteria aggregation (62), increasing the risk of periodontitis, and has also been also related to other inflammatory problems, such as obesity (63, 64).…”
Section: Discussionmentioning
confidence: 99%